Sociodemographic, lifestyle and therapeutic predictors of 2-year survival in HIV-infected persons receiving antiretroviral therapy in Benin - Charles Sossa Jerome; Maurice Agonnoudé; Ghislain Emmanuel Sopoh; Ali Imorou Bah-Chabi; Amédée de Souza; Moussa Bachabi; Gratien Gbetowenonmon; Victoire Agueh; Edgard-Marius Ouendo; Laurent Ouédraogo (AOSIS, 2017)
The benefits of antiretroviral therapy (ART) for treating human immunodeficiency virus (HIV) infection have been well described. The objective of this study was to identify the predictors of two-year survival in persons living with HIV/AIDS (PLWHA) in Benin. This retrospective transversal study included all patients from 46 HIV/AIDS therapy sites across Benin who started ART between July 1st, 2011 and June 30th, 2012. The independent variables were patients' sociodemographic, clinical, biological and therapeutic characteristics and their ART regimen. The main dependent variable was the time of death. Data were collected from medical records, using documentary review. Cox proportional hazards regression models were used to investigate factors associated with survival. Among the 771 PLWHA participants of the study, 18 (2.3%) died within the two-year period. The estimated mortality of the 771 PLWHA was 3% at 24 months. Among the sociodemographic, lifestyle and therapeutic characteristics studied, the main predictor of two-year mortality was poor adherence [odds ratio = 4.15, 95% confidence interval (1.55- 11.28)]. This study confirms that improving the survival of PLWHA receiving ART requires enhanced adherence.